International Labour Migration in Digital Era: Implementation of Indonesian Migrant Workers Placement Services - Elok Izra Yanuaryta; Damainsa Prahesti Nukyanto; Arvan Setiawan (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
This study aims to examine the implementation of Indonesian Government's policy in digitizing public services for the placement of manpower abroad. The scope of this research is focused on SIAPkerja Karirhub as a form of national digital placement service, while the research subject is limited to the performance of Ministry of Manpower which has responsibilities of manpower placement abroad and its digital services. In order to depict and explore the implementation of such digital public service, this research used a descriptive qualitative method. The results show that the regulatory framework shall be strongly considered by the government as it has a significant impact on three out of four aspects of policy implementation: communication, resources, and bureaucratic structure. While the analysis on the disposition aspect reflects a common commitment between the regulator and implementer, as well as shows the absence of friction and distortion within the Ministry of Manpower in developing and implementing the SIAPkerja-Karirhub digital service.